Is rationing of total hip arthroplasty justified? Working to optimize patient accessibility to surgery using long- term patient- reported outcome data. (2022) - Walker, R. W.; Whitehouse, S. L.; Howell, J. R.; Hubble, M. J. W.; Timperley, A. J.; Wilson, M. J.; Kassam, A- A. M.
No abstract available